Prevalence of suicidal behavior in a northeastern Mexican border population during the COVID-19 pandemic - Villarreal Sotelo, Karla; Peña Cárdenas, Fabiola; Zamorano González, Benito; Vargas Orozco, Cynthia Marisol; Hernández Rodríguez, Ignacio; Landero Pérez, Carolina (Frontiers in Psychology, 2023)
Introduction. Before the pandemic, suicide was already considered a global public health problem. The outbreak of COVID-19 coronavirus infectious disease began to impact people's physical and mental health. Research to explain the factors that drive or protect against this risk is necessary. For this reason, this work aims to study the prevalence of suicidal ideation and behavior during the COVID-19 pandemic in the population of Tamaulipas, Mexico. Method. A quantitative, descriptive, cross-sectional study was conducted. The sample consisted of a total of 663 participants, of which 195 (29.5%) were men and 465 (70.5%) between 16 and 68 years old (M=22.56, SD=7.26). An adapted version of the Spanish version of the Columbia Suicidal Severity Rating Scale to assess the seriousness of suicidal ideation and behavior was used. Results. The higher rates of suicidal indicators were suicidal ideation ranging between 39.9% “wish to be death" the higher, and Suicidal ideation with a specific plan the lower (8.2%). 18.2% of participants reported "previous to COVID-19 suicidal attempts" of whom 40% reported "suicidal attempts in the last three months". Suicidal behavior rates were lower: 13.7% of participants reported "Nonspecific preparatory behavior" and 13.3% "Actual suicide attempt". Women were at higher risk of presenting almost all indicators of suicidal ideation and behavior than men (OR = 1.63-2.54; 95% CI = 1.11-2.41, 1.76-3.68), as well as staying in confinement (OR = 2.60; 95% CI = 1.73-3.91). Knowing a person infected with COVID-19 (OR = 1.57-2.01; 95% CI = 1.02-2.42, 1.20-3.34) and confinement time greater than 40 days (OR = .55-.66; 95% CI = .40-.75, .47-.93) were associated with a higher risk to present several suicidal indicators and with previous suicidal ideas and attempts. Conclusions. Being women, knowing a person infected with COVID-19, and being in confinement specially for longer than 40 days are risk factors for presenting suicidal indicators. Intervention programs are needed to reduce the suicide risk figures, especially now due to the influence of the pandemic principally focused on those who present risk factors associated with suicidal behavior identified in this study.